Six Memos for the Current Time. Rethinking six contemporary sociological matters in light of the emotional dynamics shaping them - Alessandro Pratesi (Cambio)
This contribution is inspired by Italo Calvino’s Harvard Lectures which should had been hold at Harvard in 1986 and were never delivered because of Calvino’s sudden and premature death. Calvino began his American lectures with a series of reflections on six qualities that he considered essential for good literature and then broadened his reflections to other (no strictly literary) dimensions of our existence. This article is based on a series of reflections on six sociological subjects that I consider essential to frame the recent pandemic, and then it extends such reflections to other realms of our everyday life. Care, Welfare, Death, Politics, Europe, and Marginality: the common denominator of these different key sociological subject matters is represented by emotions and their too often unacknowledged role in interpreting and explaining contemporary phenomena. They have been chosen as they represent a number of core themes which are considered key to help us demarcating the field of our critical analyses of the pandemic, but also because they epitomise paradigmatic contexts where the political relevance of emotional dynamics vividly emerge. In this sense, the main goal of this contribution is to invite scholars from different disciplinary perspectives to further investigate these key sociological subject matters by taking into account the crucial role of emotions, shedding light on the not so visible links between micro- and macro-levels of analysis and their implications for social change, and broadening our reflections to other (no strictly sociological) dimensions of our existence.